A Tale of Two Classes: Teaching Science and Technology Reference Sources Both Traditionally and through Distance Education - Susan B. Ardis (Issues in Science and Technology Librarianship)
Teaching continuing education and credit courses has been an important and enjoyable part of my professional life. Up until this past year all my previous teaching had been the with traditional face-to-face lecture method where students come to class, take notes, do assignments, and the instructor lectures and grades.